Solutions 20 1
Solutions 20 1
Solutions 20 1
Round 1 Solutions
Year 20 — Academic Year 2008–2009
www.usamts.org
If one of the two white cubes is the central cube (that is, the cube that is not visible from
the outside), then there are only 3 distinguishable places for the other white cube to be: a
Create PDF with GO2PDF for free, if you wish to remove this line, click here to buy Virtual PDF Printer
corner, an edge, or a face-center, as shown left-to-right below:
• Two corners: 3 ways—the corners lie on opposite ends of an edge, a face diagonal, or
an interior diagonal, as shown below:
• One corner, one edge: 4 ways—the white cubes are adjacent, or give 2 non-adjacent
white squares on the same face (in two different distinguishable ways), or do not give
white squares on the same face:
• One corner, one face-center: 2 ways—either the face-center shares a face with the
corner white cube or it does not:
USA Mathematical Talent Search
Round 1 Solutions
Year 20 — Academic Year 2008–2009
www.usamts.org
• Two edges: 5 ways—there can be white squares on the same face in two ways (either
diagonally adjacent or opposite, as in the first two pictures below), or they can be on
different faces in three distinguishable ways:
• One edge, one face-center: 3 ways–the face-center may be on the same face as one of
Create PDF with GO2PDF for free, if you wish to remove this line, click here to buy Virtual PDF Printer
the white edge cube’s white squares, or the face-center is on a face adjacent to both
of the white edge cube’s white squares, or the face-center is on a face adjacent to only
one of the white edge cube’s white squares (shown left-to-right below):
(The last diagram has another white face-center on the face directly opposite the face
with the visible white face-center.)
2/1/20. Find all positive integers n for which it is possible to find three positive factors x, y,
and z of n − 1, with x > y > z, such that x + y + z = n.
Now we look for bounds on b. We already know b > a = 2. If b ≥ 4, then c > b ≥ 4, and
by (∗) we have
n+1 n−1 n−1 n−1 n−1 n−1
= + < + = ,
2 b c 4 4 2
giving a contradiction. So b < 4, and combining this with b > 2, we must have b = 3.
This means that y = (n − 1)/3, and by (∗) we get
n−1 n+1 n−1 n+5
= − = .
c 2 3 6
If c ≥ 6, then
n+5 n−1 n−1
= ≤ ,
6 c 6
giving a contradiction. Therefore, c = 4 or c = 5.
If c = 4, then
n+5 n−1
= ,
6 4
USA Mathematical Talent Search
Round 1 Solutions
Year 20 — Academic Year 2008–2009
www.usamts.org
Create PDF with GO2PDF for free, if you wish to remove this line, click here to buy Virtual PDF Printer
USA Mathematical Talent Search
Round 1 Solutions
Year 20 — Academic Year 2008–2009
www.usamts.org
3/1/20. Let a, b, c be real numbers. Suppose that for all real numbers x such that |x| ≤ 1, we
have |ax2 + bx + c| ≤ 100. Determine the maximum possible value of |a| + |b| + |c|.
Without loss of generality, we may assume that a ≥ 0. (If a < 0, then multiplying the
quadratic by −1 doesn’t affect the bound nor change the value of |a| + |b| + |c|.) Also,
replacing x by −x gives the function ax2 − bx + c and does not change the bound nor the
value of |a| + |b| + |c|. So we may also, without loss of generality, assume that b ≥ 0.
Let f (x) = ax2 + bx + c. Since f (0) = c and f (1) = a + b + c, we must have |c| ≤ 100
Create PDF with GO2PDF for free, if you wish to remove this line, click here to buy Virtual PDF Printer
and a + b + c ≤ 100. If c ≥ 0, then |a| + |b| + |c| = a + b + c ≤ 100. However, if c < 0, then
√
4/1/20. A point√P inside a regular tetrahedron ABCD is such that P A = P B = 11 and
P C = P D = 17. What is the side length of ABCD?
x2 + s2 = 11,
y 2 + s2 = 17,
√
x + y = s 2.
√
Astute
√ solvers might see “by inspection” that the solution to
√ this system is s = 3, x = 2,
y = 2 2, but we can also solve it algebraically. Using y = s 2 − x from the third equation,
substitute into the second equation:
√
17 = (s 2 − x)2 + s2
√
= 2s2 − 2 2sx + x2 + s2
√
= 2s2 − 2 2sx + 11,
where the last step above uses x2 + s2 = 11 from our earlier system of equations. Solving
for x in terms of s, we get
s2 − 3
x= √ .
s 2
Now we plug this into the first equation:
2 2
s −3
√ + s2 = 11,
s 2
and multiply through by 2s2 (to clear the denominator) and expand and simplify to get
3s4 − 28s2 + 9 = 0.
A = (a, a, a), B = (a, −a, −a), C = (−a, a, −a), D = (−a, −a, a).
√
Note that the side length is 2 2a.
Let P = (x, y, z). Then P A = P B implies that y = −z, and P C = P D implies that
y = z, so we must have y = z = 0, and hence P = (x, 0, 0).
√ click here to buy Virtual PDF√Printer
Create PDF with GO2PDF for free, if you wish to remove this line,
Computing P A = 11 and P C = 17 gives us the system
and after multiplying both sides by 4a2 , we have (3 − 2a2 )2 + 8a4 = 44a2 . This expands to
a quadratic in a2 :
12a4 − 56a2 + 9 = 0,
9
which factors as (2a2 − 9)(6a2 − 1) = 0, so a2 = 2
or a2 = 16 . But a2 = 1
6
does not give a
valid solution, so a2 = 29 , and hence a = √32 .
√ √
Therefore, the side length of ABCD is 2 2a = 2 2 √32 = 6 .
USA Mathematical Talent Search
Round 1 Solutions
Year 20 — Academic Year 2008–2009
www.usamts.org
√ √
5/1/20. Call a positive real number groovy if it can be written in the form n + n + 1 for
some positive integer n. Show that if x is groovy, then for any positive integer r, the number
xr is groovy as well.
We prove two lemmas, which we will combine to prove the overall result.
Lemma 1: If x is groovy and r is odd, then xr is groovy.
√ √ √ √
Proof: Let x = n + 1 + n and let y = n + 1 − n; note that xy = 1. Also note the
Create PDF with GO2PDF for free, if you wish to remove this line, click here to buy Virtual PDF Printer
expansions
r
r
X r √ r−k √
k
x = n+1 n ,
k=0
k
r
√ r−k √
k r k
X
r
y = (−1) n+1 n .
k=0
k
Since r is odd, adding xr and y r will cancel all of the terms in the above expansions in
which k is odd, and subtracting y r from xr will cancel all of the terms where k is even. Thus,
we see that
√ p
xr + y r = 2a n + 1 = 4a2 (n + 1), (1)
√ √
r r
x − y = 2b n = 4b2 n, (2)
where a and b are integers. Squaring each equation in the system gives us
x2r + 2 + y 2r = 4a2 (n + 1), (3)
x2r − 2 + y 2r = 4b2 n. (4)
Subtracting (4) from (3) gives 4 = 4a2 (n + 1) − 4b2 n, so 4a2 (n + 1) = 4b2 n + 4.
Then, adding (1) and (2) gives us
p √ √ √
2xr = 4a2 (n + 1) + 4b2 n = 4b2 n + 4 + 4b2 n,
√ √
and hence xr = b2 n + 1 + b2 n. Thus xr is groovy. 2
Lemma 2: If x is groovy, then x2 is groovy.
√ √
Proof : Let x = n + 1 + n. We now compute:
√ √ 2
x2 = n+1+ n
p
= n + 1 + 2 n(n + 1) + n
p
= (2n + 1) + 2 n(n + 1)
√ √
= 4n2 + 4n + 1 + 4n2 + 4n.
USA Mathematical Talent Search
Round 1 Solutions
Year 20 — Academic Year 2008–2009
www.usamts.org
So x2 is groovy. 2
a
To complete the proof, we prove that x(2 ·r) is groovy for any nonnegative integer a and
any positive odd integer r, by induction on a. The base case of the induction (where a = 0)
is Lemma 1, and the inductive step is Lemma 2.
Create PDF with GO2PDF for free, if you wish to remove this line, click here to buy Virtual PDF Printer
Credits: All problems and solutions were written by USAMTS staff. Dr. Erin Schram sug-
gested the wording for problem 2/1/20.
c 2008 Art of Problem Solving Foundation